Meningkatkan Pemahaman Konsep Siswa pada Mata Pelajaran PPKn Melalui Pengembangan Model Learning Cycle 7e Setting Peer Learning - Putri, Desi Yunita (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aimed to produce a learning cycle 7e model of peer learning settings to improve students' understanding of concepts. This study utilized research and development procedures from Plomp. The study results showed that the learning cycle 7e model of peer learning settings was valid, practical, and effective for improving students' conceptual understanding. Validity was obtained from the validation test results of learning model experts with 96.1%. In addition, the learning device expert assessed a percentage of 91% for lesson plans and a percentage of 90% for student worksheets. Furthermore, the practicality of the model tested in small groups obtained 92.7%, while the student activity with a percentage of 91.7%. Finally, the model's effectiveness obtained the average value of the pretest results of 59.8 and post-test of 93, and the student response questionnaire obtained a percentage of 91%. It indicated a significant change in students' understanding of concepts before and after implementing the developed learning model.